The Relationship Between Sexist Parenting Style and Cognitive Emotion Regulation Styles in Men With Perpetration of Domestic Violence Against Women - Aliakbari , Fatemeh; Taghvaei, Davood; Pirani, Zabih (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the relationship between sexist parenting style, cognitive emotion regulation strategies, and the perpetration of domestic violence against women by married men.Methods and Materials: A correlational design was used involving 300 married men selected through convenience sampling from medical centers in Qazvin. Participants completed the Mohseni Tabrizi Domestic Violence Questionnaire and the Garnefski Cognitive Emotion Regulation Questionnaire. Descriptive statistics, Pearson correlations, and structural equation modeling using LISREL 8.80 were conducted to analyze the data. Model fit was assessed using indices including Chi-square, RMSEA, CFI, and TLI.Findings: Results indicated that sexist parenting style was positively associated with domestic violence perpetration (β = .51, p < .001). Maladaptive cognitive emotion regulation strategies were also significantly associated with increased violent behavior (β = -.39, p < .001). Model fit indices demonstrated a good fit (χ²/df = 1.41, RMSEA = .037, CFI = .97, TLI = .96). Additionally, sexist parenting and emotion regulation interacted positively in predicting violence, suggesting that both factors jointly contribute to abusive behavior.Conclusion: The findings underscore the critical role of sexist parenting and maladaptive cognitive emotion regulation strategies in perpetuating domestic violence against women. These results highlight the need for preventive interventions focusing on gender-sensitive parenting practices and training in adaptive cognitive emotion regulation strategies among men to reduce the prevalence of domestic violence.